Uji Ekstrak Alkohol Daun Mengkudu (Morinda Citrifolia L) terhadap Konsentrasi Kreatinin dan Ureum Tikus Putih Jantan (Rattus Norvegicus) Nefropati Diabetes - Tandi, Joni; R, Yana Novika; Lakiu, Debora Rislianti; Magfira; Dewi, Niluh Puspita (Jurnal Jamu Indonesia, 2023)
Diabetic nephropathy is one of the microvascular complications of diabetes mellitus (DM). One of the clinical signs of diabetic nephropathy is an increase in urea and creatinine levels. The use of medicinal plants containing antioxidants is one of the therapeutic strategies to prevent complications of DM. The noni plant (Morinda citrifolia L), especially the leaves, contains active substances that have the potential as antioxidants to be used as supportive therapy for DM. This study aims to identify the content of active substances in noni leaf extract and determine the potential of noni leaf extract to reduce creatinine, and urea levels in diabetic nephropathy rats. Noni leaf extract was obtained by maceration using 96% ethanol, and animal models of diabetic nephropathy were obtained by induction of streptozotocin 40 mg/kg BW. The test animals were divided into six groups, namely normal control, negative control, positive control, treatment 1, 2, and 3, each given extract doses of 250, 500, and 750 mg/kg BW. The results indicated the presence of flavonoids, alkaloids, steroids, saponins, and tannins in the noni leaf extract. Giving noni leaf extract can reduce, urea and creatinine levels significantly compared to negative controls. In conclusion, noni leaf extract can potentially prevent complications of diabetic nephropathy with an effective dose of 250 mg/kg BW.